Penentuan Parameter Fisika Dan Kimia Bromelin Kasar Dari Batang Nanas (Ananas comosus Merr.) - Rieke Azhar; Budi Ariyanto; Salman Umar (STIFARM Padang, 2012)
Isolation of crude bromelain from pineapple stem has been done using phosphate buffer pH 7.0 as solvent,nthen it was centrifuged at 3,500 rpm for 15 minutes. It’s physicochemical properties then evaluated by it’s organoleptic, solubility, lost of drying, ash content, pH value, microscopic photo, particle size distribution, water absorbtion, protein qualitative and quantitative test. It’s total protein analysis done by using Mikro Kjeldahl method than gave result 8.0384% proteins.